Power profile, physiological characteristics and their correlation in elite canoe polo players - Zwingmann, L.; Hoppstock, M.; Wahl, P. (The Journal of Sports Medicine and Physical Fitness, 2020)
BACKGROUND: This study aimed to examine the physical capabilities of elite canoe polo players and to identify interrelationships between anthropometric or physiological characteristics and performance on a kayak ergometer. METHODS: Eight male participants (age 24.6±4.8 years, weight 84.1±5.3 kg, height 180.0±5.9 cm) completed four all-out time trials (15 s, 180 s, 420 s, 900 s) to determine peak power output (PPO), mean power output (MPO), maximal oxygen uptake (VO2max), maximal rate of lactate accumulation (VLamax), and maximal lactate steady-state (cMLSS). Critical power (CP) and work that can be performed above CP (W`) were assessed using a linear power model. Further, the 30-second end-test power (EP) and work done above EP (WEP) were derived from the 180 s time trial. Finally, indices were calculated from the metabolic and power data. The level of significance was set at P=0.05. RESULTS: Weak to moderate correlations were found for body weight and height compared to PPO and MPOs. VO2max correlated strongly with MPO180 and MPO420. VLamax correlated moderately with PPO and MPO15. While the calculations of CP, EP, and cMLSS correlated moderately to strongly, their means differed significantly. W` and WEP also differed significantly with a mean difference of 10.2±2.5 kJ. CONCLUSIONS: Canoe polo players are similar to sprint paddlers in their constitution, although VO2max and PPO are lower. The high correlation between physiological and power parameters also shows that simple tests that do not require blood or gas sampling can be established quickly in daily training practice.